Modern technologies in working with gifted students - Rudenko, Irina V. (2020)
Intellectual potential acts as a driving force of social and economic development of the modern state. In a high-tech society, there is a significant increase in interest in identifying and implementing the intellectual abilities of young people. The purpose of the article is to review the experience of using modern educational technologies in working with gifted students. The paper explores the implementation of innovative technologies, including games, projects, and collaborative learning technologies. The use of project and game technologies allows to develop the creative potential of students, to form an experience of research and creative activity, to activate cognitive interest by combining theory and practice. Modern educational technologies expand the opportunities for the formation and development of children's giftedness. Giftedness is a high level of development of any abilities. They are a special resource that forms the basis of the country's competitiveness and potential, which is updated as socially significant in the context of the analysis of fundamental documents in the field of education. Educational technologies allow not only to have a purposeful educational impact on students but also to create a variable, enriched, individualized educational environment that promotes the development of independence and self-learning ability.